A cost-effective 2-tier security paradigm to safeguard cloud data with faster authentication - Veena R.S; Ramachandra V. Pujeri; Indiramma M (Institute of Advanced Engineering and Science, 2019)
The recent technological advancement has taken cloud computing (CC) infrastructure to a significant level where the increasing level of research interest laid upon cost-effective storage management. Owing to the potential distributed and pervasive storage facility, it lacks efficiency towards fully preserving the integrity of user data attributes. Thereby, the collaborative sharing of user data leads to a situation which opens up various forms of security loop-holes. In the past various forms of security protocols are witnessed which have attempted to solve this similar issue with cryptographic solutions but at the same time lacks sustainability and robustness from a computational perspective. Thereby, the study introduces a 2-tier framework which offers higher-degree of access control along with Virtual Machine (VM) storage security. The study basically optimizes the performance of the model by speeding up the authentication process. The performance validation of the system has been done with respect to conventional encryption standards. The outcome obtained demonstrate that the proposed solution outperforms the existing security standards in terms of processing time, time to generate a secret key and key size for encryption.